The Effectiveness of Teaching Reading to First-grade Primary Students Using Al-Qaeda Al-Noorania from the Specialists’ Point of View in the Kingdom of Saudi Arabia: An Exploratory Study - Alwedey, Wafa Hafez; Almaghrabi, Soud Abdullah (Journal of Educational and Psychological Sciences, 2020)
The study aims to identify the effectiveness of teaching reading using the Al-Qaeda Al-Noorania Method for the first primary grade in order to resolve the dispute over the issue of teaching it for the first primary grade. To achieve the goal of the study, the two researchers followed the descriptive / reconnaissance approach, and an electronic questionnaire was designed for a survey of the study community consisting of some teachers, supervisors and supervisors of the Arabic language and specialists in teaching it in the universities of the Kingdom of Saudi Arabia Participants in the referendum reached (350) individuals, then opinions were statistically treated using percentages and repetitions, and the percentage of supporters and opponents was limited to teaching it, and the result appeared in favor of supporters by 85%. The percentage of opponents showed 15%, and one of the most important reasons for rejection is that Al-Qaeda Al-Noorania is intended for non-Arabic speakers, and the study recommended the following: by deciding that Al-Qaeda Al-Noorania should be taught in order to develop reading for the elementary grades in the primary stage and to conduct training courses for teachers aimed at raising their teaching skills to use Al-Qaeda Al-Noorania.